2019
DOI: 10.5334/aogh.2400
|View full text |Cite
|
Sign up to set email alerts
|

A Performance-Based Incentives System for Village Health Workers in Kisoro, Uganda

Abstract: Background: Village health worker (VHW) programs in Uganda have achieved limited success, due in part to a reliance on volunteerism and a lack of standardized incentive mechanisms. However, how to best incentivize VHWs remains unclear. Doctors for Global Health developed a performance-based incentives (PBI) system to pay its VHWs in Kisoro, Uganda, based on performance of tasks or achievement of targets. Objectives: 1. To describe the development of a PBI system used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…When delivering NCD care as part of a comprehensive preventative and primary care service, like the VHW program, potential cost drops. Even after incorporating the cost of initial training, our overall VHW program—the care of acute illnesses, prenatal and newborn counseling and referral, targeted health education talks, door-to-door health census, CDCom providers (not drugs), and more—costs 0.72 USD/villager [ 29 ]. While these costs seem relatively low, scaling this kind of (intensive) program nationally for 42 million people would require a substantial increase in consistent government or third-party investment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When delivering NCD care as part of a comprehensive preventative and primary care service, like the VHW program, potential cost drops. Even after incorporating the cost of initial training, our overall VHW program—the care of acute illnesses, prenatal and newborn counseling and referral, targeted health education talks, door-to-door health census, CDCom providers (not drugs), and more—costs 0.72 USD/villager [ 29 ]. While these costs seem relatively low, scaling this kind of (intensive) program nationally for 42 million people would require a substantial increase in consistent government or third-party investment.…”
Section: Discussionmentioning
confidence: 99%
“…VHW Performance-based Incentive System: Since 2010, the program has employed performance-based incentives: VHWs do not receive a base pay and are instead compensated for the performance of various activities which are validated by their supervisors twice a month [ 29 ]. Stipend amounts, varied seasonally to incentivize performance during certain periods (e.g.…”
Section: Cdcom Program Descriptionmentioning
confidence: 99%
“…Financial compensation in Kisoro is provided on a performance-based incentives (PBI) model, similar to fee-for-service, in which VHWs receive remuneration for completing tasks or achieving certain targets. Although the majority of participants indicated a preference for fixed payments, in a previous study we found that PBI incentivized health services delivery and improved accountability, which ultimately may improve acceptability by the community [ 23 24 ]. Regardless of the mechanism, the communities in this study strongly believed that VHWs should be remunerated, and the fact that they are remunerated, if not the particulars, should be made known.…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, additions have been made to the VHW program to target geriatric and mental health as well [32,33]. VHWs are paid according to a performance-based incentive system of stipends for particular activities with high public health or clinical importance, taking into account disease incidence and effort required by VHWs [34,35].…”
Section: Kisoro Uganda and The Village Health Worker Programmentioning
confidence: 99%